Work addiction and its association with personality traits, general distress, and self-esteem among adult Italian workers - Paolo Soraci; Mark D Griffiths; Francesco M Melchiori; Giulia Bravo; Eleonora Guaitoli; Elena Del Fante; Lara Scali; Francesco Grieco; Roberta Cimaglia; Carla Di Bernardo; Renato Pisanti (Mediterranean Journal of Clinical Psychology, 2022)
Background: Work addiction has become a topic of increasing research interest but has been little studied in Italy. Therefore, the aim of the present study was to investigate the associations between work addiction, assessed with a recently validated psychometric scale (i.e., Italian version of Bergen Work Addiction Scale, [BWAS]) and other psychological constructs.